2018
DOI: 10.1063/1.5053703
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced water capture induced with electrowetting-on-dielectric (EWOD) approach

Abstract: An electrowetting-on-dielectric (EWOD) device that enhances water capturing capability for condensation applications is presented. A single planar EWOD device is fabricated for testing and placed in a high-humidity environment under mist flow. By applying an electric field to portions of the device, the wettability of the affected areas is altered from hydrophobic to hydrophilic, which promotes droplet nucleation and growth, thereby improving water capturing capability. The results of this study demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These improved properties have more potential applications in the electric wetting devices.Polymers 2020, 12, 574 2 of 11 complex, and the experimental conditions are usually at high temperature and high pressure [6,7]. In order to make full use of the advantages of inorganic and polymer dielectric materials, some researchers have proposed a two-layer structure with a composite of an organic hydrophobic layer on the surface and an inorganic layer with a high dielectric constant on the bottom [6,8]. However, the manufacturing process of this structural design is more complicated.…”
mentioning
confidence: 99%
“…These improved properties have more potential applications in the electric wetting devices.Polymers 2020, 12, 574 2 of 11 complex, and the experimental conditions are usually at high temperature and high pressure [6,7]. In order to make full use of the advantages of inorganic and polymer dielectric materials, some researchers have proposed a two-layer structure with a composite of an organic hydrophobic layer on the surface and an inorganic layer with a high dielectric constant on the bottom [6,8]. However, the manufacturing process of this structural design is more complicated.…”
mentioning
confidence: 99%
“…[ 13,33 ] A series of follow‐up studies confirmed these basic original observations regarding the evolution of the drop distribution for straight interdigitated electrodes. [ 35–39 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ke et al [30] numerically studied droplet dynamics and condensation enhancement on microstructure surfaces using electrowetting to form different wettability patterns. Inspired by this study, Yan et al [79] proposed an active approach to achieve a similar objective via EWOD for water harvesting studies. Most recently, researchers have examined the electrowetting impact on condensation in terms of condensation patterns [80] and droplet shedding characteristics [81].…”
Section: Discussionmentioning
confidence: 99%
“…The contact angle variation of the EWOD devices was measured under charged (40 V DC) and uncharged conditions. The 40 V DC was chosen for safety reasons, as previous research [79] identified the safety range of applied voltage as 0-70 V DC.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
See 1 more Smart Citation